489 Assessing the Impact Of COVID-19 On Head and Neck Cancer Treatment and Preparing for The Next Wave. (12th October 2021) - Daga, K; Argus, L; Goswami, J
Abstract: Introduction: As of 11 th of March 2020, the World Health Organization (WHO) declared the novel coronavirus 2019 (COVID-19) a pandemic. It is estimated that urgent cancer referrals have reduced 70-89% across hospitals in England during the COVID-19 pandemic, in addition to reductions in attendance for the different treatment arms. The aim of our investigation is to assess the impact of COVID-19 on MDT outcomes and patients attending/receiving treatment as compared to before for head and neck cancer. Method: Data was collected retrospectively over a period of 203 days (7 th January to 28 th July 2020), including 66 patients prior to COVID-19 being declared a pandemic and 116 patients since, at a regional cancer centre. A total of 182 patients undergoing treatment were identified. These patients were assessed by TNM staging, MDT outcomes and final initial treatment intents, which were compared to pre-COVID outcomes. Results: With respect to MDT outcomes, there was an increase in the number of patients decided for surgery from 10.61% to 23.28% (p = 0.78) during the first wave of the pandemic. Patients decided for radiotherapy and chemotherapy increased by 12.49% and 4.31% respectively. Notably, there was a decrease in further investigations and referrals from 37.88% to 18.10%. Moreover, an increase in palliative treatment intent by 10.55% was noted during the pandemic. Conclusions: As the UK enters into the next peak of the pandemic, with reduced capacity for elective surgery and outpatient clinics, it is essential to consider its impact on the standard of care delivered to current cancer patients.